Indoor Positioning Method Based on Metameric White Light Sources and Subpixels on a Color Image Sensor - Heqing Huang; Aiying Yang; Lihui Feng; Guoqiang Ni; Peng Guo (IEEE Photonics Journal)
An indoor positioning method based on metameric white light sources and subpixels on a color image sensor is proposed in this paper. Metameric white light sources are obtained by merging multiple-color light-emitting diode (LED) chips with different intensity ratios. The output intensity ratios of subpixels on color image sensor at the receiver are employed to identify the respective metameric white light sources. Proof of concept experiments demonstrates that the average error of 2-D indoor positioning is 1.50 cm and 3-D indoor positioning is 3.58 cm. The indoor positioning system with the proposed method is cost effective and convenient because image sensors in nowadays available mobile devices can be utilized.